2020
DOI: 10.1002/ijc.33130
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection and the risk of cancer among the Chinese population

Abstract: The relationship between hepatitis B virus (HBV) and nonhepatocellular cancers remains inconclusive. This large case-control study aimed to assess the associations between HBV infection status and multiple cancers. Cases (n = 50 392) and controls (n = 11 361) were consecutively recruited from 2008 to 2016 at the First Affiliated Hospital of Nanjing Medical University. Multivariable adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) were estimated using logistic regression by adjusting age and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 30 publications
1
64
1
Order By: Relevance
“…Moreover, our rate of HCC patients with HBs Ag positive was 64.4% which is almost 6-fold higher than that in the United States (10%) [20]. In China, HCC are associated with cirrhosis related to chronic HBV infection in most cases [21,22]. And sustained inflammation and chronical injury can upregulate Fign mRNA expression [9].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, our rate of HCC patients with HBs Ag positive was 64.4% which is almost 6-fold higher than that in the United States (10%) [20]. In China, HCC are associated with cirrhosis related to chronic HBV infection in most cases [21,22]. And sustained inflammation and chronical injury can upregulate Fign mRNA expression [9].…”
Section: Discussionmentioning
confidence: 70%
“…The tumor physiological features are quite different. HBV-related HCC is the largest proportion of patients with HCC in China [22], while alcohol consumption and nonalcoholic steatohepatitis are the leading causes of HCC in America [21]. Thus, these inconsistent results are possibly due to the differences in demographic and HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in intrahepatic cholangiocarcinoma, the incidence of LNM in patients with HBV infection is lower than that in patients without HBV infection, which has been con rmed in some studies (24). Recent studies have reported that HBsAg positivity is also associated with the incidence and progression of other malignancies, such as gastric, esophageal, and pancreatic cancers (25). The increase in serum globulin is associated with a variety of chronic in ammatory diseases, and the increase in in ammatory cytokines in serum globulin contributes to the increase in serum albumin and the inhibition of serum albumin biosynthesis (26).…”
Section: Discussionmentioning
confidence: 85%
“…Information on general demographic and clinicopathological variables suspected to be risk factors for survival was collected for each patient. Hepatitis B virus (HBV) infection was defined by HBV sero-markers or a history of antiviral HBV treatment 28 . Hepatitis C virus (HCV) infection was confirmed by HCV-Ab positivity or a history of antiviral HCV treatment.…”
Section: Methodsmentioning
confidence: 99%